Kaji Eksperimental Efek Ketinggian Cerobong Terhadap Karakteristik Pembakaran Pada Unit Tungku Garam Semi Modern - Faisal Faisal; Khairil Khairil; Zahrul Fuadi (Jurnal Teknik Mesin Unsyiah, 2014)
Lives of traditional salt farmers increasingly concerned about the unfavorable business caused by the difficulty in obtaining fuel. The use of traditional stoves for salt farmers also without a good smoke channel, making smoke pollution that is harmful to health, and also interferes with the farmers and the environment while producing salt. Therefore, it should be considered a solution to address both of these issues by improving the combustion process that occurs in the combustion chamber and by utilizing the exhaust gas heat as a preheater in the salt process. Good combustion requires sufficient air supply with a certain excess air so that the combustion process is perfect. Air supply can be done by utilizing the natural drought affected by the height of the chimney. Utilization of flue gas has been done by creating a configuration flue gases channel through the multiport stove. Testing with chimney height variation needs to be done toget the optimal height so that stove can work with a good performance to produce salt. The results showed that the optimum height of the chimney in the semi-modern salt stove is at a height of 1.55m with a thermal efficiency of 48.6%.